Welfare and single Māori mothers in the media : symbolic power and the case of Metiria Turei : a thesis presented in partial fulfilment of the requirements for the degree of Masters of Science in Psychology at Massey University, Albany New Zealand - Martin, Ahnya (Massey University, 2020)
This thesis explores the case of Metiria Turei (former Green Party co-leader) who sparked considerable media outrage when she announced publicly that as a single mother receiving welfare decades earlier, she had taken on flat mates without notifying Work and Income New Zealand. Metiria made this announcement in an attempt to highlight current problems in the welfare system and to promote the need for systemic change. The resulting media coverage offers an interesting case of how symbolic power is used within media spaces to shape constructions of issues of poverty and welfare, and the people involved. This study involved two main empirical elements. The first was a systematic analysis of 366 television, radio and online items that made up the media public controversy surrounding Metiria’s admission. The media analysis documents how a hegemonic anti-welfare perspective came to dominate corporate news media coverage, which was contested via various social media platforms. I document how the growing pressure from conservative news commentators worked to silence both Metiria Turei and her supporters who were active on social media in promoting the need for structural changes in the welfare system. In the second element, I selected 12 key items from the media coverage of the controversy and presented these to two focus groups involving eight wāhine Māori (Māori women) who had been recipients of welfare (sole purpose benefit or domestic purpose benefit). The focus group analysis reveals how these participants challenged the narrow neoliberal framing of news coverage of Metiria Turei’s admission. Participating wāhine readily identified and deconstructed the [ill]logic of the hegemonic perspective that was dominating coverage. These participants pointed to considerable problems in the welfare system that needed to be addressed, but which, despite a few notable exceptions, were not covered in any substantive way in the corporate news coverage as a whole. Overall, this thesis showcases the changing power dynamics between corporate news and social media regarding issues of welfare and morality today.
Keywords: Low-income single mothers; Services for; New Zealand; Women, Maori; Aid to families with dependent children programs; Mass media; Influence; Political aspects; Metiria Turei; Māori Masters Thesis; 470107 Media studies